2021
DOI: 10.48550/arxiv.2106.01296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrodynamic theory of the Dyakonov-Shur instability in graphene transistors

Justin Crabb,
Xavier Cantos-Roman,
Josep M. Jornet
et al.

Abstract: We present a comprehensive theory of the Dyakonov-Shur (DS) plasma instability in currentbiased graphene transistors. Using the hydrodynamic approach, we derive equations describing the DS instability in the two-dimensional electron fluid in graphene at arbitrary values of electron drift velocity. These non-linear equations together with Maxwell's equations are used for numerical analysis of the spatial and temporal evolution of the graphene electron system after the DS instability is triggered by random curre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Furthermore, there is an agreement with Refs. [19,22] for Λ ≈ 1 (which is indeed the case for µ ≫ T ) and slow flows [35]. As we see, enforcing the boundary conditions leads to the DSI for u 0 > 0 (for Λ 1).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, there is an agreement with Refs. [19,22] for Λ ≈ 1 (which is indeed the case for µ ≫ T ) and slow flows [35]. As we see, enforcing the boundary conditions leads to the DSI for u 0 > 0 (for Λ 1).…”
mentioning
confidence: 53%
“…In addition to 2D systems, evidence of three-dimensional (3D) relativisticlike hydrodynamic electron transport was reported in the Weyl semimetal tungsten diphosphide WP 2 [17]. Because Dirac and Weyl semimetals provide a suitable platform for investigating electron hydrodynamics in solids, the DSI in graphene received a lot of attention [18][19][20][21][22]. Despite extensive theoretical studies, the generation of THz waves by the DSI was not confirmed experimentally yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation